Budaya Organisasi Memoderasi Pengaruh Efektivitas Penerapan Sia dan Kesesuaian Tugas Dengan TI Terhadap Kinerja Karyawan - Ariputra, Wayan Krisna; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi; Vol 22 No 1 (2018), 2018)
The development of information technology is very quick, making more and more innovations that appear in the field of information. Quick increased technological progress, encouraging companies to switch to the utilization of computer-based information systems because it will facilitate and accelerate management to obtain input information that will be processed in such a way that generate output information that supports a reliable decision. The purpose of this study is to determine the effect of effectiveness of the application of accounting information systems and suitability of tasks with information technology on employee performance with organizational culture as a moderator. Population in this research is employee of commerce field, finance field, and human resource field that exist in PT. PLN Distribution Bali. The background of this location is used as research place is PT. PLN Distribution Bali is a business center in the area of Bali, which is the center of the management of electricity payment throughout the area of Bali. The number of samples obtained by saturation sampling technique that is as much as 71 respondents. The number of questionnaires distributed was 71 questionnaires, and the questionnaire returned totaling 58 questionnaires. Data analysis used in this research is moderation regression analysis. This study found that the effectiveness of the application of accounting information system and the suitability of tasks with information technology have a positive effect on employee performance and organizational culture as moderator can strengthen the influence of effectiveness of application of accounting information system, conformity of tasks with information technology to employee performance. Keywords : Effectiveness application of accounting information system, task compliance, organizational culture, employee performance